Role of chlorogenic acid and procyanidin in the modification of self-assembled fibrillar gel prepared from tilapia collagen. (December 2022) - An, Xiangsheng; Duan, Shujun; Jiang, Zhicong; Chen, Sunan; Sun, Wenxuan; Liu, Xiaoyan; Sun, Zhonghao; Li, Yinping; Yan, Mingyan
Highlights: The equilibrium cross-linking degree was much higher with PC than CGA. There were primarily hydrogen bonding interactions between polyphenols and CFG. PC improved water absorption and retention capacity of gel. Mechanical properties and enzymatic resistance of gel were improved by PC. Gels showed good antioxidant and antibacterial capacity. Abstract: Collagen fibrillar gels (CFG), formed by self-assembly, displayed similar structure and properties to native tissues. Plant polyphenols showed antioxidant and antibacterial capacity, etc. Previous reports stated introduction of polyphenols could improve the properties of collagen-based material. However, only a few studies were reported on the modification of CFG by polyphenols. In the study, tilapia CFG was cross-linked with chlorogenic acid (CGA) and procyanidin (PC), respectively. The cross-linking conditions were investigated. Results showed PC endowed CFG with higher cross-linking effect at saturation than CGA. ATR-FTIR and XPS displayed there were stronger hydrogen bonds between -OH groups of PC and C = O groups of CFG, but weaker in CGA, confirmed by molecular docking simulation. XRD and SEM indicated PC induced the denser network formed by thinner fibrils, not present in CGA. As a result, water absorption and retention capacity, mechanical properties and enzymatic resistance of gel were improved evidently, whereas thermal stability reduced. Additionally, polyphenol cross-linking granted better antioxidant activity to gel, PC resulting in higher DPPH and PTIO radical scavenging ratio, while CGA showing higher Fe(II) chelation ratio. It also induced better antibacterial activity against Staphylococcus aureus, especially PC cross-linking. The results revealed CFG cross-linked by PC showed better properties compared with CGA, making it have potential application in biomaterials.